2018
DOI: 10.1111/jcmm.13651
|View full text |Cite
|
Sign up to set email alerts
|

The SHH/Gli axis regulates CD90‐mediated liver cancer stem cell function by activating the IL6/JAK2 pathway

Abstract: The cell surface antigen CD90 has recently been established as a promising marker for liver cancer stem cells. This study aimed to investigate potential implications of SHH/Gli signalling in CD90+ liver cancer stem cells. Correlation of the expression of SHH signalling components and CD90 in liver cancer cells and clinical tissues, as well as in enriched CD90+ liver cancer stem cells and the TCGA database, were analysed by quantitative RT‐PCR, Western blotting and flow cytometry. Functional analysis was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In gastric cancer cell lines and tissues, CSCs identified by the CD44 + CD24 + phenotype have demonstrated an overexpression of the SHH , PTCH1 and GLI3 genes ( 41 ). Zhang et al demonstrated that in liver cancer, CD90 + CSCs with GLI1 or GLI3 knockdown, exhibited low proliferation rates, and decreased migratory ability and sphere formation capacity, as well as a decrease in tumour formation in vivo ; indicating that both genes are relevant to the maintenance of the stem cell properties observed in CD90 + cancer cells ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer cell lines and tissues, CSCs identified by the CD44 + CD24 + phenotype have demonstrated an overexpression of the SHH , PTCH1 and GLI3 genes ( 41 ). Zhang et al demonstrated that in liver cancer, CD90 + CSCs with GLI1 or GLI3 knockdown, exhibited low proliferation rates, and decreased migratory ability and sphere formation capacity, as well as a decrease in tumour formation in vivo ; indicating that both genes are relevant to the maintenance of the stem cell properties observed in CD90 + cancer cells ( 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the SHH/GLI1 axis can activate IL-6 expression in liver cancer . The concentrations of immunosuppressive cytokine IL-10, cytokines, and chemokines IL-6, CXCL1 (GRO), and CXCL8 (IL-8) have been reported to be remarkably high in ACP .…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested as a surface marker for CSC in HCC that does not express EpCAM [ 112 , 113 ]. IL6, hedgehog, and AKT signaling pathways have been associated with CD90 [ 114 , 115 ].…”
Section: Resultsmentioning
confidence: 99%